EFFORTS TO IMPROVE THE PATROL OF THE TURJAWALI SAMAPTA UNIT TO PREVENT THE CRIME OF VIOLENT THEFT IN THE JURISDICTION OF THE POLICE OF MAGELANG - Muhammad Ghani Fikril 'Aziz (Advances in Police Science Research Journal, 2022)
The National Police as one of the state apparatuses has the task of maintaining security and order. For this reason, the Police have made various efforts, one of which is through the patrol activities of the Samapta Unit. The same was done by the Magelang Police Samapta Unit. However, with the patrols, the Magelang Police Samapta Unit is still unable to prevent the occurrence of violent theft in its jurisdiction. It is proven by the data obtained that violent theft has always been a concern in the community every year and has never decreased since 2019. Therefore, this study focuses on the implementation of the Turjawali Samapta Unit patrols of the Magelang Police in preventing the crime of violent theft. This research uses a qualitative approach with the type of field research with the research location at the Magelang Police jurisdiction. This study also uses an analytical knife of organizational management theory and organizational resources and uses concepts related to the formulated problem focus. The results of this study indicate that the patrols carried out by the Turjawali Samapta Unit of the Magelang Police, are still not optimal. This non-optimal implementation of patrols is caused by the implementation of management that is still not in accordance with the provisions and the less than optimal efforts that have been implemented. This has caused crime of violent theft in the jurisdiction of the Magelang Police in the last 3 years to never decreased. Based on the results of the study, it can be concluded that the implementation of the patrol of the Turjawali Samapta Unit of the Magelang Police is still not optimal due to management factors and organizational resources that have not been used effectively and efficiently. For this reason, it is necessary to increase the patrol of the Turjawali Samapta Unit, of the Magelang Police in preventing the crime of violent theft.